2016
DOI: 10.1093/mnras/stv2937
|View full text |Cite
|
Sign up to set email alerts
|

A SCUBA-2 survey of FeLoBAL QSOs. Are FeLoBALs in a ‘transition phase’ between ULIRGs and QSOs?

Abstract: It is thought that a class of broad absorption line (BAL) QSOs, characterised by Fe absorption features in their UV spectra (called 'FeLoBALs'), could mark a transition stage between the end of an obscured starburst event and a youthful QSO beginning to shed its dust cocoon, where Fe has been injected into the interstellar medium by the starburst. To test this hypothesis we have undertaken deep SCUBA-2 850 µm observations of a sample of 17 FeLoBAL QSOs with 0.89 z 2.78 and -23.31 M B -28.50 to directly detect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 92 publications
3
13
0
Order By: Relevance
“…Cisternas et al 2011;Kocevski et al 2012;Schawinski et al 2012;Villforth et al 2014Villforth et al , 2017Boehm et al 2012;Gabor et al 2009;Hewlett et al 2017;Grogin et al 2005) This suggest that unlike extremely red quasars (Urrutia et al 2008;Glikman et al 2015) or heavily obscured AGN (Kocevski et al 2015), FeLoBALs are consistent with the population of host galaxies of quasars of similar luminosities. This also matches findings by (Violino et al 2016) who compared the star forming properties of FeLoBAL quasars to the general quasar population and found them to be consistent.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cisternas et al 2011;Kocevski et al 2012;Schawinski et al 2012;Villforth et al 2014Villforth et al , 2017Boehm et al 2012;Gabor et al 2009;Hewlett et al 2017;Grogin et al 2005) This suggest that unlike extremely red quasars (Urrutia et al 2008;Glikman et al 2015) or heavily obscured AGN (Kocevski et al 2015), FeLoBALs are consistent with the population of host galaxies of quasars of similar luminosities. This also matches findings by (Violino et al 2016) who compared the star forming properties of FeLoBAL quasars to the general quasar population and found them to be consistent.…”
Section: Discussionsupporting
confidence: 89%
“…We analyze the host galaxies of a sample of FeLoBAL quasars and compare them to a sample of blue quasars from Villforth et al (2017). FeLoBALs, which have Fe II and other low-ionization broad absorption lines (LoBALs) (Becker et al 1997;Hall et al 2002), have been proposed as transition objects based on their typically dust-reddened colors (Dunn et al 2015) and large far-IR luminosities (indicating high star formation rates (SFRs)) (Farrah et al 2010(Farrah et al , 2012, although Violino et al (2016) found no enhanced star formation rates when compared to the general quasar population. Samples of extremely red quasars, which show high incidences of FeLoBALs, have also been found to have extremely high merger rates Urrutia et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, our results are consistent with HiBAL quasars being normal quasars observed along a particular line of sight, with the outflows in HiBAL quasars not having any measurable effect on the star formation in their hosts (see also e.g. Violino et al 2016).…”
Section: Star Formation In Broad Absorption-line Quasarssupporting
confidence: 88%
“…Bruni et al 2012;DiPompeo et al 2012DiPompeo et al , 2013. For LoBALs more frequently an evolution scenario is advocated (Boroson & Meyers 1992;Voit et al 1993), in which they constitute an early, short-lived transition phase of AGN activity, with observational support for (Boroson & Meyers 1992;Canalizo & Stockton 2002;Farrah et al 2007) and against this scenario (Lazarova et al 2012;Violino et al 2016;). The evolution scenario has been most strongly argued for the rare sub-population within the LoBAL class of FeLoBALs, which in addition also show absorption troughs in the metastable Fe II line (Hazard et al 1987;Becker et al 1997;Hall et al 2002).…”
Section: Introductionmentioning
confidence: 99%